Descriptive of Night Tooth Brushing Habits with Dental Caries Status in Grade I, II, III Children at Makassar Public Elementary School - Pannyiwi, Rahmat; Misnarliah, Misnarliah (International Journal of Health Sciences, 2025)
Dental caries is a common dental health problem in children, especially in primary school-aged children. One of the risk factors is poor tooth brushing habits, particularly neglecting to brush teeth at night before sleeping. This study aims to describe the night tooth brushing habits and their relationship with the dental caries status in Grade I, II, and III students at a public elementary school in Makassar. This descriptive study involved 90 students selected using purposive sampling. Data were collected using a structured questionnaire and clinical dental examination to assess caries status based on the DMF-T index. The results showed that 62% of the children did not regularly brush their teeth at night. Among those who did not brush at night, 78% had moderate to high dental caries. In contrast, only 22% of children who regularly brushed at night experienced similar conditions. The findings suggest a strong association between night brushing habits and caries status. Strengthening oral hygiene education for children and parents is recommended to reduce the prevalence of caries.